2013
DOI: 10.3961/jpmph.2013.46.5.271
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study on the Relationship of Sleep Duration With All-cause and Disease-specific Mortality in the Korean Multi-center Cancer Cohort Study

Abstract: ObjectivesEmerging evidence indicates that sleep duration is associated with health outcomes. However, the relationship of sleep duration with long-term health is unclear. This study was designed to determine the relationship of sleep duration with mortality as a parameter for long-term health in a large prospective cohort study in Korea.MethodsThe study population included 13 164 participants aged over 20 years from the Korean Multi-center Cancer Cohort study. Information on sleep duration was obtained throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 33 publications
10
72
3
1
Order By: Relevance
“…Spline analysis using linear models did not shown any difference in events with shorter duration than 7 hours for both cardiovascular mortality (8 studies)11, 25, 44, 47, 49, 71, 87, 88 and CVD (7 studies) 8, 12, 22, 33, 38, 42, 74. However, longer self‐reported sleep duration >7 hours appeared to be associated with a moderate increase in greater stroke mortality (cubic model shown in Data S8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spline analysis using linear models did not shown any difference in events with shorter duration than 7 hours for both cardiovascular mortality (8 studies)11, 25, 44, 47, 49, 71, 87, 88 and CVD (7 studies) 8, 12, 22, 33, 38, 42, 74. However, longer self‐reported sleep duration >7 hours appeared to be associated with a moderate increase in greater stroke mortality (cubic model shown in Data S8).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Sleep is also critically involved in systemic physiology, including metabolism, [22][23][24][25][26] appetite regulation, 27,28 immune and hormone function, [29][30][31][32][33] and cardiovascular systems. [34][35][36][37] Sleep duration is associated with mortality risk [38][39][40] and with illnesses ranging from cardiovascular 41 and cerebrovascular 42 disease to obesity, 43 diabetes, 44 cancer, 45,46 and depression. In 2013, the American Academy of Sleep Medicine and Sleep Research Society received a one year grant, renewable annually for up to five years, from the CDC entitled the "National Healthy Sleep Awareness Project."…”
Section: Introductionmentioning
confidence: 99%
“…17 They found that the U-shaped relationship was stronger in older adults (≥ 60 years) than in younger adults (< 60 years). A study including almost 60 000 Chinese participants living in Singapore, found no difference in risk of CHD deaths from short or long sleep duration between younger and older adults.…”
mentioning
confidence: 99%